Changes in structural-phase state and physicochemical properties of tungsten-free TIC-TiNi hard alloys after various types of ion-beam treatment - V. V. Akimov; A. M. Badamshin; S. N. Nesov; S. N. Povoroznyuk; A. A. Krutko; Ya. A. Sidorova (Омский научный вестник)
Using experimental methods of analysis, the morphology, elemental composition and chemical state of hard alloys of the «TiC-TiNi» system in the initial state and after various types of ion-beam treatment have been investigated. It is found that the effect of a continuous ion beam leads to an increase in the microhardness of the investigated alloys by 10–12 %. When samples are irradiated with a pulsed ion beam, as a result of destruction of surface layers, the microhardness value decreases by 20 %, as a result of which this type of modification is not preferable for alloys of the TiC-TiNi system.